2016
DOI: 10.1080/17425247.2017.1266334
|View full text |Cite
|
Sign up to set email alerts
|

Basic principles and current status of transcorneal and transscleral iontophoresis

Abstract: Iontophoresis is an active non-invasive drug delivery technique that can increase the transport of charged and neutral molecules into and across biological membranes. Most research to-date has focused on (per)cutaneous iontophoretic drug delivery. However, recent studies illustrate its potential for drug delivery to the eye: corneal iontophoresis may enable targeted topical therapy of intracorneal diseases, whereas transscleral iontophoresis may enable non-invasive intraocular drug delivery. Areas covered: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 99 publications
0
35
1
Order By: Relevance
“…The mechanism of action of iontophoresis is still under investigation. When subjected to an electric field, molecules are exposed to three transport mechanisms: passive diffusion, electromigration and electroosmosis . The passive contribution can be negligible in the eye due to its low permeability and is usually very small compared to the other two transport mechanisms; electromigration, which depends on the physicochemical characteristics, charge and concentration of the molecule is the primary electrotransport mechanism for ionized molecules (it can be considered as the ordered movement of ions in the presence of an electric field); electroosmosis produces the motion of the solvent carrying the molecule and is induced by an electric potential applied across an ionized membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of iontophoresis is still under investigation. When subjected to an electric field, molecules are exposed to three transport mechanisms: passive diffusion, electromigration and electroosmosis . The passive contribution can be negligible in the eye due to its low permeability and is usually very small compared to the other two transport mechanisms; electromigration, which depends on the physicochemical characteristics, charge and concentration of the molecule is the primary electrotransport mechanism for ionized molecules (it can be considered as the ordered movement of ions in the presence of an electric field); electroosmosis produces the motion of the solvent carrying the molecule and is induced by an electric potential applied across an ionized membrane.…”
Section: Discussionmentioning
confidence: 99%
“…P ermeation and retention of drugs in ophthalmic tissues are essential to achieve therapeutic levels sufficient to treat anterior (eg, keratitis, scleritis, anterior uveitis) and posterior (eg, diabetic retinopathy, neovascular agerelated macular degeneration, posterior uveitis) segment eye diseases. [1][2][3] When targeting the anterior segment of the eye, multiple barriers exist for topically instilled drugs even before tissue penetration, including blinking, tear film/tear mucin turnover, lacrimation, and nasolacrimal drainage. 1,[3][4][5] As a consequence, most topical ophthalmic formulations have a short residence time on the surface of the eye, and only a small proportion of the dose is available for ocular penetration.…”
Section: Introductionmentioning
confidence: 99%
“…9 Novel delivery systems continue to be investigated with the aim of developing new safe and effective ways of improving drug delivery to the eye. 2,5,6,10 Examples include enhanced drug transport using sonophoresis (ie, ultrasound), sustained release ocular drug depots, lipid-based and polymeric delivery systems, and the focus of this review, iontophoresis. This article describes the nature of ocular iontophoresis technology and reviews recent progress in the evaluation of ophthalmic drug delivery using this technology with a focus on the trans-scleral iontophoresis of dexamethasone and transcorneal iontophoresis of riboflavin.…”
Section: Introductionmentioning
confidence: 99%
“…It is then attracted to the anode (positive electrode) by the potential of the battery. Considering the cationic form of drug, the electrode polarities are reversed in this case 36,37 .…”
Section: Fig 2: Schematic Representation Of Iontophoresis Devicementioning
confidence: 99%
“…The equation demonstrated that the generated flux during iontophoresis includes: 39  Flux generated due to the electrochemical potential gradient across skin.  The effect on skin permeability due to applied electric field.…”
Section: Fig 2: Schematic Representation Of Iontophoresis Devicementioning
confidence: 99%